2019
DOI: 10.1016/j.rmed.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Mepolizumab improves small airway function in severe eosinophilic asthma

Abstract: Background and objective: Treatment with mepolizumab in severe eosinophilic asthma (SEA) significantly reduces exacerbations with modest improvements in symptom control and spirometry. The time course of any changes in small airway function is unknown. Objective: To describe changes in ventilation inhomogeneity, a marker of small airway function, after commencing mepolizumab. Methods: Prospective cohort of 20 adults (12 male) with SEA commencing monthly mepolizumab. Measurements at baseline, Week 4 and Week 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 27 publications
3
30
1
Order By: Relevance
“…Furthermore, pre-treatment IOS measures of SAD demonstrated to be meaningful predictors of clinical response, thereby indicating that severe SAD might describe a distinct phenotype with therapeutic implications among patients with severe eosinophilic asthma. Our results are consistent with the findings of previous studies which indicated that measures of SAD like FEF 25-75 , lung clearance index, regional ventilation inhomogeneity in acinar and conducting airways improve significantly under biological therapy [20,21]. Oscillometric measures of SAD seem to be feasible tools in selecting appropriate patients qualifying for anti-T2 biological therapy beyond the rather crude measurement of baseline blood eosinophils count that is frequently influenced by a multitude of factors, e.g.…”
Section: Table 2 Area Under the Curve (Auc) Of Clinical Predictorssupporting
confidence: 91%
“…Furthermore, pre-treatment IOS measures of SAD demonstrated to be meaningful predictors of clinical response, thereby indicating that severe SAD might describe a distinct phenotype with therapeutic implications among patients with severe eosinophilic asthma. Our results are consistent with the findings of previous studies which indicated that measures of SAD like FEF 25-75 , lung clearance index, regional ventilation inhomogeneity in acinar and conducting airways improve significantly under biological therapy [20,21]. Oscillometric measures of SAD seem to be feasible tools in selecting appropriate patients qualifying for anti-T2 biological therapy beyond the rather crude measurement of baseline blood eosinophils count that is frequently influenced by a multitude of factors, e.g.…”
Section: Table 2 Area Under the Curve (Auc) Of Clinical Predictorssupporting
confidence: 91%
“…Farah et al [13] assessed ventilation inhomogeneity in 20 adults with severe eosinophilic asthma, using multiple‐breath nitrogen washout to measure global (lung clearance index (LCI)) and regional ventilation inhomogeneity in acinar (Sacin) and conducting (Scond) airways. They report significant improvements in small airway function following mepolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators reported that only beclomethasone dipropionate/formoterol achieved a significant improvement in the cumulative methacholine provocation dose and a trend toward a reduction in closing capacity. 174 Farah and colleagues 175 noted that the anti-IL-5 monoclonal antibody mepolizumab was able to improve lung ventilation heterogeneity indexes in subjects with severe asthma after 26 weeks of treatment. Compared with placebo, omalizumab, a monoclonal antibody targeting serum immunoglobulin E, failed to demonstrate a significant reduction in alveolar NO in subjects with moderate to severe asthma.…”
Section: Delivery Systems Targeting Small Airwaysmentioning
confidence: 99%